Do RGPD à LGPD: difusão internacional de normas e o caso das regulamentações de proteção de dados pessoais - Muchiuti, Marília Machado (2022)
This work seeks to address the phenomenon of diffusion, analyzing the processes and forces through which norms initially restricted to a certain location end up penetrating other locations, spreading globally. The analysis is based in the case study of diffusion of norms that regulate the protection of personal data, more particularly the diffusion of European Union’s General Data Protection Regulation of 2016 (RGPD), to Brazil, which adopted a General Personal Data Protection Act in 2018 (LGPD). For this purpose, the analysis is mainly based on the “Brussels Effect” theory by author Anu Bradford – which seeks to explain European Union’s ability is exporting norms facilitated by markets, private companies, and dynamics of influence – and mainly uses the legislative process of the LGPD, as well as the content of the LGPD in comparison to the normative content of the RGPD, as its investigative resources. With the results of this analysis, the work finally debates how the process of diffusion of norms in the international system has the potential to disrupt traditional views of this system, bringing together perspectives and literatures of International Relations and Law for a holistic and integrated approach